Pengaruh Pandita Roos Telaumbanua dalam Perkembangan Agama dan Politik di Nias - Sitedi Buulolo; Muhammad Adika Nugraha; Lianda Dewi Sartika (Polyscopia, 2024)
This study examines the influential role of Pandita Roos Telaumbanua in shaping the political and religious landscape of Nias Island. Focusing on the spread of Christianity, it analyzes its impact on local social systems, including politics and culture. Utilizing a critical analysis of historical records from Pandita Roos Telaumbanua's era on Nias, the research explores the social, religious, and political consequences of his presence. Through secondary evidence, it highlights how Pandita Roos Telaumbanua significantly transformed the region's religious environment, affecting belief systems, education, and local culture. The emergence of social institutions and shifts in power dynamics within Nias society exemplify Christianity's profound influence on the regional political system. This research also underscores debates surrounding the rise of Christianity, revealing the social and political upheaval faced by Nias society. The adoption of this new religion often led to conflicts, impacting various social and political dynamics in Nias.